2022
DOI: 10.1029/2022wr032846
|View full text |Cite
|
Sign up to set email alerts
|

The Peer‐To‐Peer Type Propagation From Meteorological Drought to Soil Moisture Drought Occurs in Areas With Strong Land‐Atmosphere Interaction

Abstract: In the context of global change, drought and flood disasters are the most complex natural phenomena. Their occurrence process has the characteristics of gradualness, wide influence range, and large loss. They are considered one of the world's most serious natural disasters (Zheng, 2000), causing widespread concern among scholars and proposing positive drought mitigation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Furthermore, a noticeable lag time is observed between meteorological drought (measured by precipitation) and hydrological drought (measured by runoff and TWS). The increase in ET triggered by high AED in the early stage of drought may exacerbate soil moisture depletion and slow down the recovery of hydrological drought, although it is not the sole factor influencing the drought propagation processes (Li et al, 2022; Van Loon, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a noticeable lag time is observed between meteorological drought (measured by precipitation) and hydrological drought (measured by runoff and TWS). The increase in ET triggered by high AED in the early stage of drought may exacerbate soil moisture depletion and slow down the recovery of hydrological drought, although it is not the sole factor influencing the drought propagation processes (Li et al, 2022; Van Loon, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Study Area Propagation Type 1 Method 2 Result [27] China PMAD CA 3.4 months [28] Heihe River Basin PMAD CA Average 8 months [29] Northeast Asia PMAD CA 1-3 months in summer and 5-12 months in winter [24] North China Plain PMED CA 1.33 months in summer and 2.67 months in winter [23] China PMED CA 2.67 months in summer and 7 months in winter [25] China PMAD, PMED CA 1-2.5 months under PMAD and no delay under PMED [30] Tarim River Basin PMHD CA 2-21 months [31] India PMAD, PMHD CA 4-5 months under PMAD and 1 month shorter than that under PMHD [32] Global PMAD, PMHD CA 5.7 months under PMAD and 3.5-14.47 months under PMHD [33] Longchuan River Basin PMAD, PMHD, PHAD CA Approximately 2 months under three types of propagation [34] Yangtze River Basin PMAD, PMHD CA Less than 2 months under PMAD and 2-6 months under PMHD [35] China PMAD CA 1-2 months in summer and 2-7 months in the next spring [36] Xijiang River Basin PMHD RT Less than 3 months, with the maximum being 78 days [37] Yangtze River Basin PMAD CA 48 days [38] Luanhe River Basin PMHD CA 1-7 months in rainy season and 7-12 months in dry season [39] Huaihe River Basin PMHD RT 1-47 days [41] China PMHD CA 2-4 months 1 Propagation Type: PMAD represents the propagation from meteorological drought to agricultural drought, PMHD represents the propagation from meteorological drought to hydrological drought, PMED represents the propagation from meteorological drought to ecological drought, PHAD represents the propagation from hydrological drought to agricultural drought; 2 Method: CA represents correlation analysis, RT represents run theory.…”
Section: Referencementioning
confidence: 99%
“…To date, numerous studies have investigated the drought propagation characteristics at watershed, national and global scales (Huang et al., 2017; Q. Li et al., 2022; Ma et al., 2019, 2023; Shi et al., 2022; Xu et al., 2019; Yang et al., 2023; Zhou et al., 2021). Van Loon (2015) stated that the onsets of agricultural and hydrological droughts were usually later than that of meteorological drought, and concluded that the drought propagation could be characterized by pooling, lagging, attenuation and lengthening.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies have investigated the drought propagation characteristics at watershed, national and global scales (Huang et al, 2017;Q. Li et al, 2022;Ma et al, 2019Ma et al, , 2023Shi et al, 2022;Xu et al, 2019;Yang et al, 2023;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%